NLRP3 Inflammasome: A Possible Link Between Obesity-Associated Low-Grade Chronic Inflammation and Colorectal Cancer Development - Ahechu, Patricia; Zozaya, Gabriel; Martí, Pablo; Hernández-Lizoáin, José Luis; Baixauli, Jorge; Unamuno, Xabier; Frühbeck, Gema; Catalán, Victoria (Frontiers in Immunology, 2018)
Emerging evidence indicates that adipose tissue inflammation is an important mechanism whereby obesity promotes colorectal cancer risk and progression. Increased inflammasome activity in adipose tissue has been proposed as an essential mediator of obesity-induced inflammation and the development of insulin resistance. Chronic inflammation in tumor microenvironments is not only associated with tumor development, but also has significant impact on tumor immunity and response to therapy. In this context, the inflammasomes, main components of the innate immune system, play an important role in cancer development showing tumor promoting or tumor suppressive actions depending on the type of tumor, the specific inflammasome involved, and the downstream effector molecules. The inflammasomes are large multiprotein complexes best known for their ability to regulate the activation of caspase 1. In turn, caspase 1 enhances the proteolytic cleavage and the secretion of the inflammatory cytokines interleukin (IL)-1 and IL-18, leading to infiltration of more immune cells and resulting in the generation and maintenance of an inflammatory microenvironment surrounding cancer cells. The inflammasomes also regulate a rapid and inflammatory form of cell death named pyroptosis. Recent studies indicate that the inflammasomes can be activated by fatty acids and high glucose levels linking metabolic danger signals to the activation of inflammation and cancer development. These data suggest that activation of the inflammasomes may represent a crucial step in the obesity-associated cancer development. This review will also focus on the potential of inflammasome-activated pathways to develop new therapeutic strategies for the prevention and treatment of obesity-associated colorectal cancer development.